Virtual Adventure: A Digital Fun Book Utilizing Problem-Based Learning in IPAS for Fifth Grade Subject on Ecosystems Harmony - Ni Putu Metha Metha; Anak Agung Gede Agung; Komang Alit Wahyuni (Jurnal Ilmiah Sekolah Dasar, 2025)
Low learning outcomes in ecosystem material are due to limited variation in media and methods, emphasizing the need for interactive, problem-based learning innovations. This study aims to develop, evaluate the feasibility, and assess the effectiveness of a virtual adventure-based digital fun book based on Problem-Based Learning. Employing a Research and Development approach, the study adopts the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). Research subjects include experts in Development and Design, content, instructional design, learning media, and 21 fifth-grade students. Data were collected using Likert-scale questionnaires and multiple-choice tests, then analyzed with descriptive and inferential statistics. The findings indicate that the developed media demonstrates excellent quality (scores >90%) based on expert validation and product trials. Furthermore, the t-test results (tcalculated = 2.041 > ttable = 1.724) confirm a statistically significant improvement in learning outcomes. In conclusion, the virtual adventure-based digital fun book using PBL effectively boosts student motivation, engagement, and learning outcomes in ecosystem topics. This media serves as an alternative for interactive, contextual learning that fosters critical thinking and can be adapted for other topics within the Merdeka Curriculum.